Black Sunday : a novel - Abraham, Tola Rotimi (Catapult, 2020)
"Twin sisters Bibike and Ariyike are enjoying a relatively comfortable life in Lagos in 1996. Then their mother loses her job due to political strife, and the family, facing poverty, becomes drawn into the New Church, an institution led by a charismatic pastor who is not shy about worshipping earthly wealth. Soon Bibike and Ariyikes father wagers the family home on a “sure bet” that evaporates like smoke. As their parents marriage collapses in the aftermath of this gamble, the twin sisters and their two younger siblings, Andrew and Peter, are thrust into the reluctant care of their traditional Yoruba grandmother. Inseparable while they had their parents to care for them, the twins paths diverge once the household shatters. Each girl is left to locate, guard, and hone her own fragile source of power."--Publisher's website.